COVD-11. THE BRAIN TUMOR AND NOT FOR PROFIT AND CHARITY EXPERIENCE OF COVID 19: REACTING AND ADJUSTING TO AN UNPRECEDENTED GLOBAL PANDEMIC IN THE 21ST CENTURY. (9th November 2020) - Ellen Maher, Mary; Amidei, Christina; Arzbaecher, Jean; Oliver, Kathy; Mungoshi, Christine; Cashman, Rosemary; Farrimond, Stuart; Kruchko, Carol; Granero, Anita; Tse, Chris; Daniels, Maureen; Lovely, Mary; et al.
Abstract: The COVID-19 pandemic has not only affected individuals, but also disease specific not-for-profits and charities. Brain tumor not-for-profit and charitable organizations around the world exist in all shapes and sizes, and address unmet needs of the patients and caregivers they serve. The International Brain Tumor Alliance(IBTA) carried out an international survey to identify organization changes brought about by the virus and the approaches adopted to address operational challenges created by COVID-19. A 37-question survey was sent across the world. In total, 77 organizations from 22 countries responded. Descriptive statistics and content analysis were used to present RESULTS: Responses fell into three categories: 1) organizational characteristics, 2) the impact of COVID-19 on services, and 3) how COVID-19 has affected the financial and human resources in these organizations. Although organizational characteristics vary widely, common concerns reported across organizations were primarily: a) the disruption of activities which impacted organizations' abilities to offer their usual services and b) challenges to sustaining funding. Although brain tumor organizations have been impacted by the COVID-19 pandemic, organizations quickly adjusted to this unprecedented global healthcare crisis.